Advanced and invasive cardiopulmonary resuscitation (CPR) techniques as an adjunct to advanced cardiac life support - Obermaier, Manuel; Katzenschlager, Stephan; Kofler, Othmar; Weilbacher, Frank; Popp, Erik (Journal of Clinical Medicine, 2022)
Background: Despite numerous promising innovations, the chance of survival from sudden cardiac arrest has remained virtually unchanged for decades. Recently, technological advances have been made, user-friendly portable devices have been developed, and advanced invasive procedures have been described that could improve this unsatisfactory situation. Methods: A selective literature search in the core databases with a focus on randomized controlled trials and guidelines. Results: Technical aids, such as feedback systems or automated mechanical cardiopulmonary resuscitation (CPR) devices, can improve chest compression quality. The latter, as well as extracorporeal CPR, might serve as a bridge to treatment (with extracorporeal CPR even as a bridge to recovery). Sonography may be used to improve thoracic compressions on the one hand and to rule out potentially reversible causes of cardiac arrest on the other. Resuscitative endovascular balloon occlusion of the aorta might enhance myocardial and cerebral perfusion. Minithoracostomy, pericardiocentesis, or clamshell thoracotomy might resolve reversible causes of cardiac arrest. Conclusions: It is crucial to identify those patients who may benefit from an advanced or invasive procedure and make the decision to implement the intervention in a timely manner. As with all infrequently performed procedures, sound education and regular training are paramount.
Gesehen am 25.01.2023